2015
DOI: 10.1530/joe-14-0711
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic and reproductive benefits of early dietary energy restriction and voluntary exercise in an obese PCOS-prone rodent model

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common endocrine-metabolic disorders in women of reproductive age characterized by ovulatory dysfunction, hyperandrogenism and cardiometabolic risk. The overweight-obese PCOS phenotype appears to have exacerbated reproductive dysfunction and cardiometabolic risk. In overweight-obese adult women with PCOS, exercise and energy restricted diets have shown limited and inconsistent effects on both cardiometabolic indices and reproductive outcomes. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Regarding dietary intervention, thus far, no caloric restricted diet has been recommended in the guidelines. Early initiation of exercise alone, or in combination with dietary energy restrictions, helps in improving reproductive and metabolic indicators in women with PCOS and obesity [ 1 , 6 ]. Also, weight loss alone is insufficient in treating PCOS in women with normal BMI [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding dietary intervention, thus far, no caloric restricted diet has been recommended in the guidelines. Early initiation of exercise alone, or in combination with dietary energy restrictions, helps in improving reproductive and metabolic indicators in women with PCOS and obesity [ 1 , 6 ]. Also, weight loss alone is insufficient in treating PCOS in women with normal BMI [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
“…The molecular mechanism underlying the efficacy of lifestyle interventions and its effects was recently explained in a rodent model study [ 6 ]. It appears to be mediated through the normalization of the hypothalamic neuropeptides (cocaine and amphetamine-regulated transcript (CART) and Kisspeptin), and plasma sex-hormone binding globulin (SHBG) [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…Intervention with flutamide, an androgen receptor (AR) inhibitor, has confirmed that testosterone action via the AR mediates apoB-hyperlipoproteinemia and hypertriglyceridemia, and this appears to be independent of effects on insulin ( 110 ). Fasting plasma apoB100, apoB48, and TG concentrations were lowered by 25–50% in animals treated with flutamide.…”
Section: The Female Jcr:la-cp Rat As a Model Of Pomentioning
confidence: 99%
“…Additionally, the intestinal secretion of TG, cholesterol, and the cholesterol/apoB48 and TG/apoB48 (a marker of lipid per CM particle secreted from the intestine) were markedly reduced following flutamide treatment. Hepatic and intestinal lipogenic gene expression showed that flutamide may lower hepatic SREBP-1, LDLR, and HMGCR in PCOS-prone animals ( 110 ). Interestingly, PCOS-prone animals have reduced IR, MAPK1, AKT2, and PTPN1 mRNA expression in the intestine, but not the liver.…”
Section: The Female Jcr:la-cp Rat As a Model Of Pomentioning
confidence: 99%
See 1 more Smart Citation